Antioxidant Activity of Clay Mask Stick with Premna serratifolia L. Extract Using Green Solvents - Nurmala Sari; isnindar isnindar; Nera Umilia Purwanti (Sam Ratulangi University, Manado, Indonesia, 2026)
Buas-buas leaves are a medicinal plant containing flavonoids and phenolic compounds with potential antioxidant activity to protect the skin from damage caused by free radicals. The use of green solvents has emerged as an alternative in developing safer and more sustainable cosmetic formulations. This study aimed to determine the IC₅₀ value of buas-buas leaf extracts obtained using green solvents and to formulate the most active extract into a clay mask stick preparation. Extraction was carried out using the MAE method with natural honey mixed with distilled water (1:20) and NADES based on citric acid and glucose (1:1). Antioxidant activity of both extracts and formulations was evaluated using the DPPH method to determine IC₅₀ values. The extract with the best activity was then formulated and further evaluated for physical and chemical stability using a cycling test method. The results showed that the NADES extract exhibited very strong antioxidant activity with an IC₅₀ value of 31.53 ppm, while the natural honey extract showed moderate activity with an IC₅₀ of 108.53 ppm. The clay mask stick formulations on day 0 had IC₅₀ values of 207.94 ppm (F1) and 171.57 ppm (F2), categorized as weak, and 110.88 ppm (F3), categorized as moderate. After six cycles of the cycling test, IC₅₀ values increased to 434.28 ppm (F1) and 312.55 ppm (F2), categorized as very weak, and 208.48 ppm (F3), categorized as weak, indicating decreased antioxidant activity after accelerated storage. However, all formulations remained physically stable and had pH values within a safe range for skin.